Caring and resources in older age - Argyle, Elaine (2003)
Due to the high incidence of ill health and disability amongst their contemporaries, older people are likely to be involved in informal caring relationships. Due to the limited nature of post-retirement incomes, such carers are also likely to be relatively poor. In spite of this, little attention has been given to the role of older carers or to the influence of material deprivation upon this role. Drawing on fieldwork interviews with a sample of older co-resident carers and the secondary analysis of official statistics, this research aims to redress this ‘ageless’ and ‘classless’ analysis of informal care. While the original intention of the research was to focus solely on the way in which material resources went on to affect caring in older age, subsequent analysis revealed a complex interaction between material circumstances, physical pathology, culture and attitude. The concept of resources was therefore broadened to incorporate these issues and the study’s materialist focus has been supplemented by a consideration of the age-based specificity in the way in which respondents manage and experience their financial situation and caring role. The thesis concludes with a consideration of the implications of these findings for future policy, literature and research. Thus, it is suggested that in view of the high degree of interdependence in caring relationships, intervention should focus less on the conflicting needs of care providers and care receivers and more on their commonality and their shared need for adequate and appropriate support. Similar synthesis is required in the exploration of poverty, older age and caring and also in the three generations of thought that have engaged in this exploration. In the light of this synthesis, it is argued that the ‘relative autonomy’ of the age dynamic should be recognised and responded to by researchers, practitioners and policy makers alike.